Super-amphiphobic coating with durable wear resistance and corrosion resistance on surface of aluminum alloy and preparation method of super-amphiphobic coating
By using nano-scale silicon dioxide and titanium dioxide particles, PTFE and epoxy resin on the surface of the aluminum alloy, a super double-sparse coating is formed, which solves the problem of the surface of the aluminum alloy being easily corroded in the marine environment, and achieves long-lasting wear resistance. Anti-corrosion and anti-fouling effects.
Patent Information
- Application Number
- CN202411618284.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The surface of aluminum alloy is susceptible to corrosion in the marine environment, and traditional surface treatment methods are difficult to effectively improve their wear resistance and corrosion resistance.
The combination of nanoscale silica and titanium dioxide particles, polytetrafluoroethylene (PTFE) and epoxy resin matrix is used to deposit and bake and cure by electrophoresis to form a super double-sparse coating.
It realizes the long-lasting wear-resistant, anti-corrosion and anti-fouling properties of the aluminum alloy surface, enhances the hardness and wear resistance of the coating, and has superhydrophobic and superoleophobic properties, which can provide long-term protection in harsh environments.
Smart Images

Figure CN119463629A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a super-amphiphobic coating on an aluminum alloy surface with durable wear resistance and corrosion resistance and a preparation method thereof. Background Art
[0002] Aluminum alloy has various advantages such as light weight, good thermal and electrical conductivity, good plasticity and formability, easy processing, etc. It is widely used in aerospace, automobile manufacturing, electronic manufacturing, instrument manufacturing, light industrial building materials and many other fields. Especially in recent years, the rapid development of my country's industry has high requirements for lightweight, energy saving and emission reduction. Nowadays, aluminum alloy can replace steel in many aspects and become a widely used metal material in industrial development. However, the surface of aluminum alloy contains other metal elements such as Mg and Zn, which are more chemically active, especially in the presence of active Cl - It is more susceptible to corrosion in marine environments with high concentrations of oxygen and dissolved oxygen, which seriously limits its service life and application areas. With the improvement of industrial requirements, its shortcomings such as low hardness, poor wear resistance and corrosion resistance are becoming increasingly prominent. Therefore, how to effectively improve the wear resistance and corrosion resistance of aluminum alloy surfaces has become an important issue that needs to be solved urgently.
[0003] Traditional surface treatment methods, such as electroplating, anodizing and organic coating, have improved the wear resistance and corrosion resistance of aluminum alloys to a certain extent, but there are still some shortcomings. For example, the electroplating layer is prone to cracks during long-term use, resulting in a decrease in corrosion resistance; the anodized layer is prone to wear in a friction environment; and the organic coating is prone to failure in high temperature or strong acid / alkali environment. In recent years, super-amphiphobic surfaces have attracted widespread attention due to their special surface wettability, which can reduce the interaction between interfaces, especially in the fields of corrosion resistance, ice prevention, anti-fouling and oil-water separation. Super-amphiphobic coatings fundamentally reduce the possibility of corrosion and friction by reducing the contact area between liquid and solid surface, and can prevent liquid adhesion and reduce surface contamination. However, achieving long-lasting wear resistance and corrosion resistance of coatings on aluminum alloy surfaces remains a huge challenge.
[0004] The invention patent with publication number CN117210094A proposes a super-amphiphobic composite coating with wear resistance, heat conduction and corrosion resistance and its preparation method. The composite coating components include 8-10 parts of flake graphite, 8-10 parts of Al-2O-3, 1-3 parts of long-chain silane coupling agent, 15-20 parts of fluorine-containing resin particles, 70-80 parts of solvent, and 30-35 parts of epoxy resin by weight, wherein epoxy resin is used as a film-forming material, fluorine-containing resin is used as a low surface energy material, and long-chain silane coupling agent can improve the mechanical properties and film-forming properties of the coating. The coating achieves excellent wear resistance, thermal conductivity and corrosion resistance through a unique material ratio and preparation process. However, the low surface energy modified flake graphite and low surface energy modified spherical alumina and other high-performance materials used in the preparation process of the coating are relatively expensive, and the modification steps involved in the preparation process of the coating are complicated, which not only increases the production cost and the difficulty of popularizing the technology, but also may reduce production efficiency, and is not suitable for promotion and application.
[0005] Publication number is the invention patent of CN114703456A, proposes a novel corrosion-resistant super-hydrophobic coating and preparation method thereof on a kind of aluminum and aluminum alloy surface, specifically: aluminum or aluminum alloy is successively processed by cleaning pretreatment, impregnation and pulling coating, in-situ chemical curing treatment to achieve uniform adhesion of coating and effectively enhance the bonding force of the two interfaces, so as to obtain a novel corrosion-resistant super-hydrophobic coating of super stability. But there are metal salts such as copper, chromium, nickel in the coating preparation process, which may pollute the environment, especially chromium salts, and some of its forms (such as hexavalent chromium) have high toxicity, and if improperly handled, chemical waste liquid may cause serious harm to the environment, and is not suitable for application. Summary of the invention
[0006] In order to solve the above problems, the purpose of the present invention is to provide a super-amphiphobic coating on the surface of aluminum alloy with durable wear resistance and corrosion resistance and a preparation method thereof.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] In the first aspect, the present invention provides a super-amphiphobic coating on the surface of an aluminum alloy with durable wear resistance and corrosion resistance, which comprises the following components by weight: 10-15 parts of nano-scale silicon dioxide particles, 10-15 parts of nano-scale titanium dioxide particles, 5-10 parts of polytetrafluoroethylene (PTFE), and the remaining weight percentage of an epoxy resin matrix as a carrier. The combination can effectively provide durable anti-corrosion, anti-fouling and wear resistance.
[0009] The average particle size of the nano-scale silicon dioxide particles (SiO2) is 20-22nm, and the concentration is 1-1.5wt%; the average particle size of the nano-scale titanium dioxide particles (TiO2) is 25-28nm, and the concentration is 0.5-0.6wt%; the average particle size of the polytetrafluoroethylene (PTFE) powder is 200-220nm, and the concentration is 0.5-0.6wt%. The nano-scale silicon dioxide particles and the nano-scale titanium dioxide particles jointly provide super hydrophobic and super oleophobic properties, while the addition of polytetrafluoroethylene (PTFE) enhances the wear resistance of the coating and reduces the surface energy, so that the coating has super amphiphobic properties and increases its antifouling ability.
[0010] In a second aspect, the present invention provides a method for preparing a super-amphiphobic coating on an aluminum alloy surface having durable wear resistance and corrosion resistance, comprising the following steps:
[0011] S1) mixing the nanoparticles with the modifier, stirring or ultrasonically dispersing the nanoparticles so that the modifier is evenly coated on the surface of the particles, and then removing unreacted residues by washing to obtain charged nanoparticles;
[0012] S2) mixing the surface-modified nano-scale silicon dioxide particles, the modified nano-scale titanium dioxide particles, polytetrafluoroethylene (PTFE) powder and the epoxy resin matrix to form a premixed solution;
[0013] S3) using ultrasonic dispersion technology to treat the premixed liquid to ensure that the modified nanoparticles and PTFE are evenly dispersed in the epoxy resin matrix to form a stable suspension system.
[0014] S4) The components in the premixed liquid are uniformly deposited on the surface of the aluminum alloy by electrophoresis: the pretreated aluminum alloy material is placed in an electrophoresis tank, and appropriate electric field parameters are adjusted to allow the charged particles in the premixed liquid to be uniformly deposited on the surface of the aluminum alloy to form a uniform coating.
[0015] S5) taking out the aluminum alloy material from the electrophoresis tank and rinsing it with deionized water to remove excess sediment;
[0016] S6) baking the prepared aluminum alloy plate at 80-120° C. to cure it, thereby obtaining a super amphiphobic coating.
[0017] In the step S1), the proportions of the raw material components are: 10-15 parts of modified silicon dioxide particles, 10-15 parts of modified titanium dioxide particles, 5-10 parts of polytetrafluoroethylene PTFE powder, and the remaining 60-75 parts of the epoxy resin matrix as a carrier. The modifier is an aminosilane coupling agent (such as one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane) or a positively charged polymer (one or more of polyethyleneimine, polydimethyldiallyl ammonium chloride, and ribopolysaccharide).
[0018] In the step S2), the ultrasonic dispersion time is 30-35 min and the ultrasonic power is 200-220 W to ensure that the nanoparticles in the premix are evenly dispersed.
[0019] In the step S3), the pretreatment of the aluminum alloy material includes surface cleaning and micro-roughening treatment to increase the adhesion strength between the coating and the aluminum alloy surface; the conductivity of the premixed liquid in the electrophoresis tank is 100-110 μS / cm, the electrophoresis voltage is 50-55V, and the electrophoresis time is 10-12min.
[0020] The baking process in step S5) adopts a gradual heating method to avoid aggregation of nanoparticles in the premixed liquid due to rapid heating, thereby ensuring the uniformity and performance stability of the coating.
[0021] In the technical solution of the present invention, the micro-nano structure formed by polytetrafluoroethylene in the coating can effectively reduce friction and reduce surface wear. In particular, the strong van der Waals force between PTFE molecules ensures that a sliding effect can be provided when the surface is rubbed. When the coating surface is rubbed, the interaction between PTFE molecules enables the PTFE molecular layer to slide relatively easily when subjected to external forces. In addition, the fluorine atoms on the surface of PTFE form an almost completely smooth surface, further reducing friction. Nano-scale silica and titanium dioxide particles have better compatibility with epoxy resins, and can form a dense protective layer on the surface of the coating, which can not only block corrosive media, but also generate free radicals by ultraviolet irradiation through the photocatalytic effect of titanium dioxide, destroy organic matter adsorbed on the surface of aluminum alloy, and further prevent the occurrence of corrosion. At the same time, nano-scale silica and titanium dioxide particles form a multi-level rough structure of micrometer to nanometer level on the surface, and PTFE provides the necessary low surface energy. These factors work together to increase the contact angle between the droplet and the coating surface, so that water and oil droplets form beads when they touch the coating, instead of spreading, to achieve a self-cleaning effect. Its core innovations are mainly reflected in the following aspects:
[0022] 1. Innovation in material combination: The raw materials of the coating of the present invention include nano-sized silica particles, nano-sized titanium dioxide particles, polytetrafluoroethylene (PTFE) and epoxy resin matrix. In traditional coatings, although nano-silicon dioxide and titanium dioxide have been used in wear-resistant and hydrophobic and oleophobic coatings, many researchers have not conducted in-depth research on the performance improvement brought about by the fine control of the particle size range. The present invention achieves the best micro-nano surface structure effect by optimizing the particle size of nano-silicon dioxide (20-22nm) and nano-titanium dioxide (25-28nm). This combination can effectively provide long-lasting anti-corrosion, anti-fouling and wear-resistant properties, especially through the synergistic effect of nano-scale silica and titanium dioxide particles and epoxy resin. The nano-particles of silica and titanium dioxide can form a micro-nano-level rough structure on the surface of epoxy resin due to their tiny particle size, thereby increasing the proportion of gas attached to the coating surface, forming an "air bag" effect, and the combination of micro-nano structure and low surface energy material increases the contact angle of water and oil, forming a super-hydrophobic and super-oleophobic coating. This additional "barrier layer" increases the path for corrosive media (such as water and oxygen) to penetrate under the coating, thereby improving the corrosion resistance of the coating. In addition, silica and titanium dioxide nanoparticles themselves have high hardness (especially titanium dioxide has a higher hardness), and when dispersed in the epoxy resin matrix, they can effectively enhance the hardness and wear resistance of the entire coating, and when the coating is rubbed or scratched, the nanoparticles act as "blockers" to reduce the wear of the material surface. Secondly, nanoparticles can also disperse stress in the matrix and reduce crack propagation caused by local stress concentration.
[0023] 2. Innovation in preparation process: The present invention uses electrophoresis to evenly deposit the components in the premixed liquid on the surface of the aluminum alloy, and through a specific baking temperature and baking curing process, the stabilization of the coating is achieved at a lower temperature, so that the particles and the matrix are more closely combined, avoiding the damage to the material properties caused by excessively high temperatures, and ensuring the uniformity and performance stability of the coating. Compared with the spray coating method, the electrophoresis method has significant advantages in the uniformity, density and adhesion of the coating: ① During the electrophoresis process, the charged particles move in a fixed direction under the action of the electric field and are deposited on the substrate, so that the particles can be closely stacked with each other, reducing the porosity of the coating; ② The electric field strength and deposition time of the electrophoretic deposition method can be precisely controlled to obtain a uniform coating thickness. Since the charged particles are subjected to relatively uniform force in the electric field, the coating thickness is uniform, the edges are smooth, and good coverage can be achieved on surfaces with complex shapes; ③ Electrophoretic deposition usually occurs in a solution, and the coating material is gradually deposited under the action of the electric field to form a strong interfacial bonding force. During the deposition process, the particles gradually approach the substrate material, and the layer-by-layer deposition method results in higher mechanical interlocking forces and intermolecular interactions between the coating and the substrate.
[0024] 3. Performance improvement: The coating of the present invention has the characteristics of high wear resistance, high hardness, and super hydrophobicity and oleophobicity. By pre-treating the surface of the aluminum alloy, a stable and dense coating film is formed to isolate oxygen to improve the corrosion resistance of the coated surface. This coating can provide long-lasting protection in harsh environments and has important application value.
[0025] 4. Environmental friendliness: The electrophoretic deposition method is a closed system that can recycle unused deposited materials. The utilization rate of the materials in the entire process is close to 100%. Compared with traditional surface treatment methods, the coating provided by the present invention is pollution-free during production and use, and the process flow is simple, which not only reduces production costs, but also reduces the impact on the environment, and has good environmental friendliness.
[0026] In summary, the innovation of the present invention is mainly reflected in the innovation of material combination, innovation of preparation process, improvement of performance and environmental friendliness, etc. These innovations together constitute the important contribution of the present invention in the field of coating technology.
[0027] The advantages and beneficial effects of the present invention are as follows:
[0028] The coating provided by the present invention is pollution-free during production and use and has a simple process flow. The prepared coating has a high cross-linking density and a low curing shrinkage rate, and has the characteristics of high wear resistance, high hardness, and super hydrophobicity and oleophobicity. At the same time, by pre-treating the surface of the aluminum alloy, a stable and dense coating film is formed, which can isolate oxygen to improve the corrosion resistance of the coated surface, so that it can provide sustainable and long-term protection to the coated surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Contact angle images of water and oil droplets dropped onto super-amphiphobic coatings; including: water (left), (sunflower oil) (right).
[0030] Figure 2 The contact angle change diagram of the coating after 200 cycles of friction. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings.
[0032] A super-amphiphobic coating on the surface of an aluminum alloy with long-lasting wear resistance and corrosion resistance comprises the following components by weight: SiO2 accounts for 10-15 parts, TiO2 accounts for 10-15 parts, PTFE accounts for 5-10 parts, and an epoxy resin matrix as a carrier accounts for the remaining weight percentage. The combination can effectively provide long-lasting anti-corrosion, anti-fouling and wear resistance.
[0033] The average particle size of SiO2 is 20-22nm, and the concentration is 1-1.5wt%; the average particle size of TiO2 is 25-28nm, and the concentration is 0.5-0.6wt%; the average particle size of PTFE powder is 200-220nm, and the concentration is 0.5-0.6wt%. SiO2 and TiO2 together provide super hydrophobic and super oleophobic properties, while the addition of PTFE enhances the wear resistance of the coating and reduces the surface energy, so that the coating has super amphiphobic properties and increases its antifouling ability.
[0034] In this coating, a high-performance, multifunctional coating system is formed mainly through the synergistic effect of PTFE, SiO2, TiO2 and epoxy resin. The multi-level rough structure of SiO2 and TiO2 on the surface at the micron to nanometer level, together with the PTFE with low surface energy, can achieve a self-cleaning effect of the coating. This feature is of great significance for improving the durability and maintenance convenience of the coating in harsh environments.
[0035] The preparation method of the super amphiphobic coating comprises the following steps:
[0036] S1) mixing SiO2, TiO2, PTFE powder and epoxy resin matrix to form a premixed solution;
[0037] S2) ensuring uniform dispersion of the nanoparticles in the premixed solution by ultrasonic dispersion technology;
[0038] S3) placing the pretreated aluminum alloy material into an electrophoresis tank, and uniformly depositing the components in the premixed solution on the surface of the aluminum alloy by electrophoresis;
[0039] S4) taking out the aluminum alloy material from the electrophoresis tank and rinsing it with deionized water to remove excess sediment;
[0040] S5) baking the prepared aluminum alloy plate at 80° C. to 120° C. to cure it, thereby obtaining a super amphiphobic coating.
[0041] The prepared super-amphiphobic coating was tested for contact angle according to the provisions of the standard GB / T 26490-2011 "Test method for super-amphiphobic performance of nanomaterials" to obtain its super-amphiphobic performance; the coated test piece was tested for corrosion resistance according to the provisions of GB / T 10125-2012 "Artificial atmosphere corrosion test salt spray test", and the corrosion was accelerated and tested by continuous spraying with a neutral NaCl solution; the wear resistance of the coating was tested according to GB / T 23988-2009 "Falling sand method for determination of wear resistance of coatings", and the super-hydrophobic coating sample was cyclically rubbed with 1000 mesh SiC sandpaper under a load of 200g, and the moving distance of each cycle was 10cm.
[0042] Example 1
[0043] Super amphiphobic coating I includes the following components: SiO2 10g, TiO2 10g, PTFE 5g and epoxy resin 60g.
[0044] The preparation method of the super-amphiphobic coating I is as follows: 1) taking appropriate amounts of SiO2, TiO2, and PTFE powders and mixing them with an epoxy resin matrix to form a premixed liquid; 2) ensuring that the nanoparticles in the premixed liquid are evenly dispersed by ultrasonic dispersion technology; 3) placing the pretreated aluminum alloy material in an electrophoresis tank, and depositing the components in the premixed liquid evenly on the surface of the aluminum alloy by electrophoresis; 4) taking the aluminum alloy material out of the electrophoresis tank, and rinsing it with deionized water to remove excess sediment; 5) baking and curing the obtained aluminum alloy plate at 80° C. to 120° C. to obtain the super-amphiphobic coating I.
[0045] Example 2
[0046] Super amphiphobic coating II includes the following components: SiO2 10g, TiO2 12.5g, PTFE 7.5g and epoxy resin 67.5g.
[0047] The preparation method and use method of the super-amphiphobic coating II are the same as those in Example 1 to obtain a super-amphiphobic coating II.
[0048] Example 3
[0049] Super amphiphobic coating III includes the following components: SiO2 10g, TiO2 15g, PTFE 10g and epoxy resin 75g.
[0050] The preparation method and use method of the super-amphiphobic coating III are the same as those in Example 1 to obtain a super-amphiphobic coating III.
[0051] Example 4
[0052] Super amphiphobic coating IV includes the following components: SiO2 12.5 g, TiO2 10 g, PTFE 7.5 g and epoxy resin 75 g.
[0053] The preparation method and use method of the super-amphiphobic coating IV are the same as those in Example 1 to obtain a super-amphiphobic coating IV.
[0054] Example 5
[0055] Super amphiphobic coating V includes the following components: SiO2 12.5 g, TiO2 12.5 g, PTFE 10 g and epoxy resin 60 g.
[0056] The preparation method and use method of the super-amphiphobic coating V are the same as those in Example 1, and a super-amphiphobic coating V is obtained.
[0057] Example 6
[0058] Super amphiphobic coating VI includes the following components: SiO2 12.5 g, TiO2 15 g, PTFE 5 g and epoxy resin 67.5 g.
[0059] The preparation method and use method of the super-amphiphobic coating VI are the same as those in Example 1 to obtain a super-amphiphobic coating VI.
[0060] Example 7
[0061] Super amphiphobic coating VII includes the following components: SiO2 15g, TiO2 10g, PTFE 10g and epoxy resin 67.5g.
[0062] The preparation method and use method of the super-amphiphobic coating VII are the same as those in Example 1 to obtain the super-amphiphobic coating VII.
[0063] Example 8
[0064] Super amphiphobic coating VIII includes the following components: SiO2 15g, TiO2 12.5g, PTFE 5g and epoxy resin 75g.
[0065] The preparation method and use method of the super-amphiphobic coating VIII are the same as those in Example 1 to obtain the super-amphiphobic coating VIII.
[0066] Example 9
[0067] Super amphiphobic coating IX includes the following components: SiO2 15g, TiO2 15g, PTFE 7.5g and epoxy resin 60g.
[0068] The preparation method and use method of the super-amphiphobic coating IX are the same as those in Example 1 to obtain a super-amphiphobic coating IX.
[0069] According to the test method described above, the performance of the super-amphiphobic coating prepared in each embodiment was tested, and the performance test results are shown in Table 1.
[0070] Figure 1 The contact angle image of water and oil (sunflower oil) dropped onto the superamphiphobic coating is shown. Figure 2 The contact angle change graph of the coating after 200 cycles of friction is shown. After 200 cycles of friction, the water contact angle WCA of the coating is greater than 150°, and it still maintains excellent water repellency, indicating that the coating has excellent superhydrophobic properties and friction resistance.
[0071] From the coating performance test results, it can be concluded that the comprehensive performance of the super-amphiphobic coating III in Example 3 is the best, which is specifically manifested as follows: after 200 cycles of friction, the water contact angle WCA of the coating is greater than 150° (159.4°), no corrosion occurs in the salt spray test for 2000 hours, and the coating does not bubble, wrinkle, fall off, or crack, and has excellent and lasting hydrophobicity, oleophobicity, wear resistance, and corrosion resistance. (The test results of hydrophobicity, oleophobicity, and wear resistance are all characterized by contact angle values, where wear resistance is the contact angle value after 200 cycles of friction; in the test results of corrosion resistance, "excellent" means no corrosion occurs, and "good" means the corrosion area is less than 3%)
[0072] Table 1 Coating performance test results
[0073]
Claims
1. A super-amphiphobic coating on the surface of an aluminum alloy with long-lasting wear resistance and corrosion resistance, characterized in that: The invention comprises the following components in parts by weight: 10-15 parts of modified silicon dioxide particles, 10-15 parts of modified titanium dioxide particles, 5-10 parts of polytetrafluoroethylene (PTFE), and 60-75 parts of an epoxy resin matrix as a carrier.
2. The super-amphiphobic coating on the surface of aluminum alloy according to claim 1, characterized in that: The average particle size of the modified silicon dioxide particles SiO2 is 20-22nm, and the concentration is 1-1.5wt%; the average particle size of the modified titanium dioxide particles TiO2 is 25-28nm, and the concentration is 0.5-0.6wt%.
3. The super-amphiphobic coating on the surface of aluminum alloy according to claim 2, characterized in that: The average particle size of the polytetrafluoroethylene (PTFE) powder is 200-220nm, and the concentration is 0.5-0.6wt%; the polytetrafluoroethylene (PTFE) enhances the wear resistance of the coating and reduces the surface energy, so that the coating has super-amphiphobic performance and increases its anti-fouling ability.
4. A method for preparing a super-amphiphobic coating on an aluminum alloy surface according to claim 3, characterized in that: The following steps are involved: S1) mixing the nanoparticles with the modifier, stirring or ultrasonically dispersing the nanoparticles so that the modifier is evenly coated on the surface of the particles, and then removing unreacted residues by washing to obtain charged nanoparticles; S2) mixing the surface-modified nano-scale silicon dioxide particles, the modified nano-scale titanium dioxide particles, the polytetrafluoroethylene powder and the epoxy resin matrix to form a premixed solution; S3) using ultrasonic dispersion technology to treat the premixed liquid to ensure that the modified nanoparticles and polytetrafluoroethylene are evenly dispersed in the epoxy resin matrix to form a stable suspension system; S4) uniformly depositing the components in the premixed solution on the surface of the aluminum alloy by electrophoresis: placing the pretreated aluminum alloy material in an electrophoresis tank, adjusting appropriate electric field parameters, so that the charged particles in the premixed solution are uniformly deposited on the surface of the aluminum alloy to form a uniform coating; S5) taking out the aluminum alloy material from the electrophoresis tank and rinsing it with deionized water to remove excess sediment; S6) baking the prepared aluminum alloy plate at 80-120° C. to cure it, thereby obtaining a super amphiphobic coating.
5. The preparation method according to claim 4, characterized in that: in the step S1), the proportions of the raw material components are: 10-15 parts of modified silicon dioxide particles, 10-15 parts of modified titanium dioxide particles, 5-10 parts of polytetrafluoroethylene (PTFE) powder, and the remaining 60-75 parts of the epoxy resin matrix as a carrier.
6. The preparation method according to claim 4, characterized in that: in the step S1), the modifier is an aminosilane coupling agent or a positively charged polymer.
7. The preparation method according to claim 4 is characterized in that: the aminosilane coupling agent is one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane; the positively charged polymer is one or more of polyethyleneimine, polydimethyldiallylammonium chloride, and ribopolysaccharide.
8. The preparation method according to claim 7, characterized in that: in the step S2), the ultrasonic dispersion time is 30-35 min, and the ultrasonic power is 200-220 W, so as to ensure that the nanoparticles in the premix are evenly dispersed.
9. The preparation method according to claim 8 is characterized in that: in the step S3), the pretreatment of the aluminum alloy material includes surface cleaning and micro-roughening treatment to increase the adhesion strength between the coating and the aluminum alloy surface; the conductivity of the premixed liquid in the electrophoresis tank is 100-110 μS / cm, the electrophoresis voltage is 50-55 V, and the electrophoresis time is 10-12 min.
10. The preparation method according to claim 9 is characterized in that: the baking process in step S5) adopts a gradual temperature increase method to avoid aggregation of nanoparticles in the premixed liquid due to rapid heating, thereby ensuring the uniformity and performance stability of the coating.
Citation Information
Patent Citations
Novel corrosion-resistant super-hydrophobic coating on surfaces of aluminum and aluminum alloy and preparation method of novel corrosion-resistant super-hydrophobic coating
CN114703456A
Wear-resistant, heat-conducting and anti-corrosion super-amphiphobic composite coating and preparation method thereof
CN117210094A
Self-cleaning coating with oleophobic and hydrophobic characteristics
CN113045952A
Wear-resistant super-hydrophobic nano composite coating and preparation method thereof
CN116179047A
Member with ultrawater-repellent surface
JP1998237431A
Cited By
Corrosion-resistant and wear-resistant sealing ring and preparation method thereof
CN120484314A